FinanzArchiv / Public Finance Analysis (JSTOR)
The FinazArchiv/Public Finance Analysis deals with all aspects of public finance. Special emphasis is on German and foreign fiscal and tax policy.
Keywords: Business, Business & Economics, Economics, Finance